A social-cognitive model of animal cruelty - Henry, Bill (Psychology, crime & law, 2018)
Recent decades have seen the emergence of social cognitive models of interpersonal aggression. These models, which have focused primarily on childhood aggression, have been the subject of extensive theoretical, methodological, and empirical attention. More recently, researchers have used social cognitive models to address adult interpersonal aggression as well as child abuse and neglect. This article will discuss the ways in which researchers can potentially extend this model to understand the abuse and neglect of animals. After a brief review of the literature on social-information processing, schemas, and normative beliefs about aggression, I will apply these mechanisms and findings to what we know about animal cruelty. I will also use current social cognitive models of aggression to describe potential directions for future research within the field of animal abuse and neglect scholarship.